Art Activities to Enhance Media Information and Digital Literacy (MIDL) for Primary Students - Po Ngern, Wisud (ASEAN Journal of Education, 2023)
Thailand’s economic, social and cultural development is taking place within a burgeoning era of media information technology. Unsurprisingly, the move to ensure Thailand’s general population is proficient in Media Information and Digital Literacy (MIDL), is considered essential for civic development by Thai authorities. Arguably, to promote critical thinking and independent learning as student competencies within the Basic Education Core Curriculum B.E. 2551, MIDL is of even greater importance: in today’s rapidly changing society, for example, IT skills are crucial to navigate, interact with and make sense of local, national and international cultures. This article presents the results of research into “Media Information and Digital Literacy when used in (primary) teaching and learning contexts and applied to art-based learning activities: four distinct but connected areas were sampled: 1. Media information access (2) Analysis, Criticize and Evaluate media (3) Create content and information and (4) Reflect and Act. Overall, 56.00 % of all students in the study had prior knowledge of using MIDL, increasing to 89.58 % after completing the research activity. All students were satisfied with the MIDL activity. The sampled case studies were undertaken by grade 5 students at “Ban Lamphaya school” Muang, Nakhon Pathom.